Clinical evaluation of adjunctive topical therapy HCl 25 mg in surgical periodontal flap - Sutamaya, Agus; Hendiani, Ina; Susanto, Agus (Universitas Padjadjaran, 2016)
Introduction: HCl tetracycline has been used as adjunctive therapy in surgical flap for chronic periodontitis. The aim of this study was to investigate the effect of tetracycline HCl 25 mg as an adjunctive therapy in surgical flap to reduce pocket depth and gingival inflammation. Methods: Subjects are divided into 2 groups, surgical flap group with tetracycline HCl 25 mg and surgical flap only. Measurements of pocket depth and gingival inflammation were taken in first condition and 1 month after treatment. Result: flap surgical treatment with a tetracycline Hcl 25 mg given topically provides better results for pocket depth and gingival inflammation in patients with chronic periodontitis. Pocket measurements and gingival inflammation 1 month after surgery compared with early conditions showed significant differences (p = 0.00 and p = 0.00). Conclusion: Based on our study it was found that the use of tetracycline HCl 25 mg topically has a better influence in reducing pocket depth and gingival inflammation in chronic periodontitis.